Cevaplar

2012-11-10T21:01:39+02:00

a)(+1).(+7)=(+7).(+1)=(+7)’dır.
b)(+1).( -9)=(-9).(+1)=(-9) ‘dur.
c)(+1).0=0.(+1)=0’dır

a)0.(+5)=(+5).0=0’dır
b)0.(-4)=(-4).0=0 dır.

d)(+3).(-4).(+5)=[(+3).(-4)].(+5)
=(-12).(+5)
= (-60)

1)(+3).(-4).(+5)=(+3).[(-4).(+5)] 
=(+3).(-20)
=(-60)

2)(+2).(-3).(+5).(-5)=[(+2).(-3)].[(+5).(-5)]
=(-6).(-25)
= -150

3)(+2).(-3).(+5).(-5)=[(+2).(+5)].[(-3).(-5)]
=(+10).(-15)
=(-150)

4)a)(+2).(+2).(+2)=[(+2).(+2)].(+2)
=(+4).(+2)
=(+6)
b)(-3).(-3).(-3).(-3)=[(-3).(-3)].[(-3).(-3)]
=(-6).(-6)
=36
c) (+5).(+5)=25
d)(+40).(+40).(+40)=[(+40).(+40)].(+40)
=(+160).(+40)
=(+6400)
e) (-2).(+19)=(-38) f) (+25).(+12)=(+300)
g)(+3).(-6).(-4).(-5)=[(+3).(-6)].[(-4).(-5)]
=(-18).(+20)
=(-360)
h) (+6).(+6).(-5).(-1)=[ (+6).(+6)].[(-5).(-1)]
=(+36).(+5)
=(+180)


a)(+3).(-7).(-5)=(+3).[(-7).(-5)]
=(+3).(+35)
=(+105)
b)(-8).(+7).(-2)=[(-8).(-2)].(+7)
=(+16).(+7)
=(+112)
c)(-2).(-1).(+3).(-4)=[(-2).(-1).(-4)].(+3)
=(+8).(+3)
(+24)
d)(+9).(-5).(-7).0=0

0